Show that v(x, y;a, b)= (x+y)[2xy+(a-b)(x-y)+2ab]/(a+b)3 is the Reimann function for second order pde uxy + (2/x+y)(ux + uy)=0
"L(u)=u_{xy}+a(x,y)u_x+b(x,y)u_y+c(x,y)u=f(x,y)"
"L^*(v)=v_{xy}-(av)_x-(bv)_y+cv"
Condition of Riemann's function:
"L^*(v)=0"
"v_x=\\frac{2xy+(a-b)(x-y)+2ab}{(a+b)^3}+\\frac{(x+y)[2y+(a-b)]}{(a+b)^3}"
"v_{xy}=\\frac{2x-(a-b)}{(a+b)^3}+\\frac{2y+(a-b)}{(a+b)^3}+\\frac{2(x+y)}{(a+b)^3}=\\frac{4(x+y)}{(a+b)^3}"
"a(x,y)v=b(x,y)v=2\/(x+y)\\cdot (x+y)[2xy+(a-b)(x-y)+2ab]\/(a+b)^3="
"=2[2xy+(a-b)(x-y)+2ab]\/(a+b)^3"
"cv=0"
"(av)_x=\\frac{2(2y+(a-b))}{(a+b)^3}"
"(bv)_y=\\frac{2(2x-(a-b))}{(a+b)^3}"
"L^*(v)=\\frac{4(x+y)}{(a+b)^3}-\\frac{2(2y+(a-b))}{(a+b)^3}-\\frac{2(2x-(a-b))}{(a+b)^3}=0"
Comments
Leave a comment